GENERALIZATION OF THE IDENTIFICATION METHOD OF LINEAR DYNAMIC SYSTEMS USING PULSE SIGNAL - Romantsev, I. O.; Rybalka, R. V.; Havryliuk, V. I. (Science and Transport Progress, 2009)
The modification of identification method for linear systems by pulse response that extends its use area is offered. The research results on example of a linear dynamic stationary discrete system are presented.